Speaking pictures : neuropsychoanalysis and authorship in film and literature - Fox, Alistair (Indiana University Press, 2016)
Alistair Fox presents a theory of literary and cinematic representation through the lens of neurological and cognitive science in order to understand the origins of storytelling and our desire for fictional worlds. Fox contends that fiction is deeply shaped by emotions and the human capacity for metaphorical thought. Literary and moving images bridge emotional response with the cognitive side of the brain. In a radical move to link the neurosciences with psychoanalysis, Fox foregrounds the interpretive experience as a way to reach personal emotional equilibrium by working through autobiographical issues within a fictive form.